SURG-37. SYSTEMATIC REVIEW OF GAMMA-KNIFE RADIOSURGERY AND MICROSURGICAL RESECTION FOR BRAINSTEM CAVERNOUS MALFORMATIONS - Kondajji, Aditya (Neuro Oncol, 2020)
BACKGROUND: Although microsurgical resection (MR) remains the gold-standard for the treatment of symptomatic cavernous malformations, some authors have proposed the use of radiosurgical Gamma-Knife Surgery (GKS) for lesions that are deep or eloquent, such as those located in the brainstem. OBJECTIVE: Here were analyze the literature regarding patient outcomes following MR or GKS for brain stem cavernous malformations. METHODS: This study was conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines for systematic literature review. A database search of PubMed, Scopus, Embase, and Web of Science was conducted in September 2019. This review included studies evaluating the outcomes of MR or GKS for cavernous malformations located in the brainstem. RESULTS: Gross total resection was achieved in the majority of patients and effectively eliminated the risk of recurrent hemorrhage from the operative lesion in studies following the outcomes of MR. GKS reduces the annual hemorrhage rate for patients, although it does not eliminate the cavernous malformation. Both treatment modalities were effective in reducing prior symptomatology. Unlike resection, GKS only reduces the risk of future hemorrhage and does prevent it. CONCLUSIONS: Both MR and GKS can improve or stabilize symptoms in patients. However, the therapeutic benefit of GKS may take months to years to take full-effect, resulting in a potential for subsequent hemorrhagic events. MR remains the best treatment option due to its ability to eliminate future bleeding events entirely and should be performed whenever gross total resection is possible.